Study on the correlation between radioactive counting time and measurement uncertainty of ceramic materials. Issue 4 (2nd October 2022) - Wei, Hong; Wen-Jie, Li; Xiao-Wei, Weng; Yi-qin, Zhang; Xiao-Hui, Liu; Wen-Chao, Xu; Hao, Tian; Ming, Wang
ABSTRACT: This paper sketched the basic principles of ceramic materials radioactivity measurement and mathematical calculation formula of testing time. When the sample measurement conditions and the way of data analysis are constant, using sodium iodide gamma spectrometer for getting the radioactive spectra data of 5 groups of samples. In condition of the background count time tb or sample measurement time ts increasing gradually, study the radioactivity specific activity measurement error range of all samples. It is derived when the background count rate of nb and sample counting rate ns is constant, the measurement error ν 2 and the sum of reciprocal of the background count time tb and reciprocal of the sample measuring time ts for approximately linear positive correlation. The measurement error of 226 Ra, 232 Th, 40 K radioactive specific activity of different ceramic samples presents the corresponding fluctuations as their initial energy spectrum count rate differences. This study for coordination of the contradiction between ceramic materials radioactive measurement time and the uncertainty has certainly theoretical and practical value.